Coronary intervention door-to-balloon time and outcomes in ST-elevation myocardial infarction: a meta-analysis. Issue 16 (5th February 2018) - Foo, Chee Yoong; Bonsu, Kwadwo Osei; Nallamothu, Brahmajee K; Reid, Christopher M; Dhippayom, Teerapon; Reidpath, Daniel D; Chaiyakunapruk, Nathorn
Abstract : Objective: This study aims to determine the relationship between door-to-balloon delay in primary percutaneous coronary intervention and ST-elevation myocardial infarction (MI) outcomes and examine for potential effect modifiers. Methods: We conducted a systematic review and meta-analysis of prospective observational studies that have investigated the relationship of door-to-balloon delay and clinical outcomes. The main outcomes include mortality and heart failure. Results: 32 studies involving 299 320 patients contained adequate data for quantitative reporting. Patients with ST-elevation MI who experienced longer (>90 min) door-to-balloon delay had a higher risk of short-term mortality (pooled OR 1.52, 95% CI 1.40 to 1.65) and medium-term to long-term mortality (pooled OR 1.53, 95% CI 1.13 to 2.06). A non-linear time– risk relation was observed (P=0.004 for non-linearity). The association between longer door-to-balloon delay and short-term mortality differed between those presented early and late after symptom onset (Cochran's Q 3.88, P value 0.049) with a stronger relationship among those with shorter prehospital delays. Conclusion: Longer door-to-balloon delay in primary percutaneous coronary intervention for ST-elevation MI is related to higher risk of adverse outcomes. Prehospital delays modified this effect. The non-linearity of the time– risk relation might explain the lack of population effect despite an improved door-to-balloon time in the USA. Clinical trial registration: PROSPERO (CRD42015026069).